The Influence Of Students’ Attitude Towards Economics As A Course Of Study On Academic Performance In University Of Lagos, Lagos State - Filade, Bankole Adeyemi; Omozokpia, Davidson Osagie; Uwannah, Ngozi; Amanze, Samuel; Ajibola, Iyadunni Esther; Omotosho, Tominiyi (Advances in Social Sciences Research Journal, 2020)
The decline in students’ academic performance in Economics as a course of study in the last decade is worrisome. This study therefore seeks to investigate influence of students’ attitude towards Economics as a course of study on academic performance in the University of Lagos. The study adopted descriptive survey research design and made use of a sample of One hundred and twenty (120) undergraduate students randomly selected from Economics Education cohort, Faculty of Education, University of Lagos, Akoka. A self-developed questionnaire of 34 items was used to collect information from the students after its validity and reliability (r=0.68) were determined with the use of split half method. The data collected were analysed using Mean, Standard Deviation, and Simple Percentage while Chi-square, independent t-test and One-way Anova statistical tools were used to analyse three hypotheses at 0.05 level of significance using (SPSS) testing program. The study revealed that there is significance influence of students’ attitude towards economics as a course on academic performance. Both male and female students have almost the same attitude towards economics as a course. Also, the attitude of students towards economics as a course is the same at different academic levels. In the light of the study`s results, the researchers presented a number of recommendations and proposals the most important of which are: Ministry of education should organize orientation programmes against wrong attitude of undergraduate students towards economics as a course in order to improve their motivation and academic performance. Since gender does not affect the attitude of students towards economics as a course, teaching and learning of economics as a course should be done freely among the students of different sexes. Seminars and symposiums should be organized by university management for Economics department, Faculty of Education about the prospects of the course to motivate them towards academic excellence.